2019
DOI: 10.1002/ecs2.2843
|View full text |Cite
|
Sign up to set email alerts
|

Adding invasive species biosurveillance to the U.S. Geological Survey streamgage network

Abstract: The costs of invasive species in the United States alone are estimated to exceed US$100 billion per year, so a critical tactic in minimizing the costs of invasive species is the development of effective, early-detection systems. To this end, we evaluated the efficacy of adding environmental (e)DNA surveillance to the U.S. Geological Survey (USGS) streamgage network, which consists of >8200 streamgages nationwide systemically visited by USGS hydrologic technicians. Incorporating strategic eDNA sample collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 50 publications
(100 reference statements)
1
42
0
Order By: Relevance
“…We used previously published assays, limits of detection and methods therein for analyses of Naegleria spp. 12 , T. bryosalmonae 13 , S. japonicas 15 , O. nerka 7 , and Dreissena spp. 16 ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used previously published assays, limits of detection and methods therein for analyses of Naegleria spp. 12 , T. bryosalmonae 13 , S. japonicas 15 , O. nerka 7 , and Dreissena spp. 16 ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the ubiquity of eDNA in the aquatic environment, eDNA of targeted taxa is not always well mixed, so high detection probabilities often require intense sampling 5 , 6 . Therefore, reliable detection requires trained individuals to manually collect water samples over long time periods or across large geographic areas 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Water was collected by trained technicians from one water body with established zebra mussel populations (San Justo Reservoir, CA), one water body with established quagga mussel populations (Lake Mead, NV), two water bodies with established populations of both zebra and quagga mussels (Lake Michigan, WI, and Seneca Lake, NY), and three water bodies where zebra or quagga mussel presence has not been documented (Jackson Lake, WY; the Yellowstone River, MT; and the Columbia River, OR; Figure 1). The individuals that collected samples varied by location (Table 1), but we trained all field technicians in US Geological Survey (USGS) eDNA sampling protocols (Sepulveda, Schmidt, et al 2019).…”
Section: Edna Water Collection Filtration and Dna Extractionmentioning
confidence: 99%
“…Importantly, we found that multiple assays that each target different genomic locations (e.g., 16s ribosomal subunit, mitochondrial Cyt B and COI regions) were all high performing. Analyzing a single sample with a suite of assays that target different genomic locations has been suggested as a way to improve the accuracy and rigor of eDNA monitoring programs (Farrington et al, 2015 (Sepulveda, Schmidt, et al 2019). Another, more cost-effective, option involves assay suites combined into multiplex reactions, though Gingera et al (2017) did find performance of the DRE16s, ZEBCOI, and ZEBCYT diminished when incorporated into the same multiplex reaction.…”
Section: Detection Proportions As Functions Of Assays Water Body mentioning
confidence: 99%
“…Environmental DNA (eDNA) surveys continue to gain popularity for detecting invasive, cryptic and rare species (Klymus, Richter, Chapman, & Paukert, 2015; Lodge et al., 2012; Schmelzle & Kinziger, 2016; Sepulveda et al., 2019), as these techniques are often easier, less expensive and more sensitive than non‐molecular detection tools (Eiler, Löfgren, Hjerne, Nordén, & Saetre, 2018; Hunter, Meigs‐Friend, Ferrante, Smith, & Hart, 2019; Sengupta et al., 2019; Sepulveda et al., 2019; Williams, Huyvaert, Vercauteren, Davis, & Piaggio, 2018). These surveys rely on hierarchical sampling techniques to accommodate spatial heterogeneity in the occurrence of DNA within a study region.…”
Section: Introductionmentioning
confidence: 99%